Windows server 2008 R2 Hyper-V insiders guide to Microsoft's Hypervisor - Kelbley, John 1967-; Sterling, Mike 1977- (Hoboken, NJ Wiley, 2010)
"Get the inside scoop on Hyper-V for Windows Server 2008 R2. Virtualization is a top priority for thousands of companies all over the world. Written by an author team that is part of the Windows virtualization group at Microsoft, Windows Server 2008 R2 Hyper-V will walk you through Hyper-V essentials so you can get you up to speed and down to business with Hyper-V. Now fully updated for Windows Server 2008 R2 Hyper-V, you will find additional content on new features and capabilities such as Live Migration and support for 64 Logical Processors (LP). Teaches how to manage virtual machines with the latest System Center tools such as Virtual Machine Manager 2008 R2, Data Protection Manager 2010, and Operations Manager 2007 R2. Covers all of the new functionalities of Windows Server 2008 R2 Hyper-V, including Live Migration, 64 LP support, Processor Compatibility Mode, enhanced processor functionality support, hot-add and remove of storage, TCP Offload support, and VM Queue support. Demonstrates key scenarios for Hyper-V, including server consolidation, testing and development, Business Continuity and Disaster Recovery, and Dynamic IT. Provides step-by-step instructions and examples. This insiders guide will help you get the most out of your hardware and reduce cost with Windows Server 2008 R2 Hyper-V."--
Includes index
1 12
Keywords: Microsoft Windows server Hyper-V; Virtual computer systems